A method for producing high-purity and high-sphericity iron powder by hydrogen reduction-consolidation method

Through the combined process of low-temperature hydrogen reduction and dynamic high-temperature consolidation, the problems of whisker growth and agglomeration during high-temperature reduction are solved, and spherical iron powder with high spherical shape, high fluidity, and high purity are prepared, reducing production costs and increasing production costs Product performance.

CN118905233BActive Publication Date: 2024-12-20CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411424082.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2024-12-20
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

In the preparation of high spherical iron powder in the prior art, the problems of whisker growth and agglomeration during the high-temperature reduction process are difficult to control, resulting in poor spherical and fluidity, and high cost, making it difficult to meet the needs of high-end products.

Method used

The combination process of low-temperature hydrogen reduction and dynamic high-temperature consolidation is adopted to avoid whisker growth through low-temperature reduction, and a dynamic roasting furnace and reasonable cooling conditions are used during the high-temperature consolidation process to reduce the risk of agglomeration, the difficulty of dispersion and yield are significant. improve.

Benefits of technology

High-purity spherical iron powder with high spherical shape, smooth surface and good fluidity is obtained, which reduces production costs, avoids the loss of steel strips by high-temperature treatment, and improves the application prospects of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118905233B_ABST
    Figure CN118905233B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for producing high-purity and high-sphericity iron powder by hydrogen reduction-consolidation method, which belongs to the technical field of ultrafine iron powder preparation. The method is to obtain spherical agglomerates by ultrafine grinding-spray drying of iron oxide raw materials, and the obtained spherical agglomerates are first placed in a reduction furnace for low-temperature hydrogen reduction, and then placed in a dynamic roasting furnace for high-temperature consolidation to obtain spherical iron powder agglomerates, and the spherical iron powder agglomerates are dispersed by ultrasound to obtain spherical iron powder. The method can obtain spherical iron powder with the characteristics of high sphericity, high fluidity, high density, high purity, etc., which meets the application requirements of advanced manufacturing fields such as MIM injection molding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing micro-nano spherical iron powder, in particular to a method for producing high-purity and high-sphericity iron powder by a hydrogen reduction-solidification method, belonging to the technical field of ultrafine iron powder preparation. Background Art

[0002] Spherical powders are increasingly widely used in many fields because of their good fluidity and high tap density. Taking spherical iron powder as an example, in the field of powder metallurgy, the molded parts prepared by it have high density, and the molded parts shrink evenly during the sintering process, which can obtain higher precision and performance than conventional iron powder products, especially in advanced manufacturing such as injection molding and 3D printing. It has obvious advantages. At present, the methods for preparing spherical iron powder with high sphericity are only gas atomization and carbonyl methods. It is very difficult to further refine the particle size of the products, and the cost is more than 30,000 yuan / ton. The high cost has largely limited its wide application in the industry. The relatively cheap water-atomized iron powder is difficult to meet the needs of high-end products in terms of sphericity and morphology. It is urgent to develop a more suitable spherical iron powder preparation technology.

[0003] A Chinese patent (publication number: CN116833417A) discloses a method for producing spherical iron powder by hydrogen reduction, which comprises the following steps: subjecting the iron oxide raw material to ultrafine wet grinding to obtain an ultrafine particle slurry; spray drying the ultrafine particle slurry to obtain spherical agglomerates; subjecting the spherical agglomerates to hydrogen reduction at a temperature of 750-850°C to obtain a reduction product, and the reduction product is ultrasonically dispersed to obtain spherical iron powder. This method can obtain spherical iron powder by one-step high-temperature reduction and consolidation, and has the characteristics of simple process, but the conditions for completing both reduction and consolidation are harsh, and the operation is difficult to control, especially the high reduction temperature, which makes it easy for whiskers to form on the surface of the iron powder particles and affect the improvement of sphericity. At the same time, the iron powder agglomerates more seriously after high-temperature reduction treatment, and the energy consumption required in the subsequent dispersion process is large, and the sphericity of the iron powder will be affected. Summary of the invention

[0004] In view of the defects and shortcomings of the prior art, the purpose of the present invention is to provide a method for producing high-purity and high-sphericity iron powder by hydrogen reduction-consolidation method, which can obtain spherical iron powder with micro-nano particle size and no whiskers on the surface, showing the characteristics of high sphericity, high density, smooth surface, good fluidity, etc., and is particularly suitable for advanced manufacturing fields such as injection molding. The method divides the high-temperature reduction process into a low-temperature reduction process and a high-temperature consolidation process, each of which specifically undertakes corresponding tasks. The low-temperature reduction effectively avoids the growth of whiskers in the high-temperature reduction process of iron powder, and improves the surface morphology of the spherical iron powder sphere, which is conducive to obtaining a product with high sphericity, high fluidity and smooth surface. The sphericity index can reach the level of high-quality carbonyl iron powder. At the same time, a dynamic process is adopted in the high-temperature consolidation process, which can effectively reduce abnormal agglomeration during high-temperature treatment, significantly improve the dispersion strength and yield rate required for the subsequent dispersion process, and avoid the loss of steel strips in the steel strip furnace. In the production process, only high-grade iron sources and solvent media need to be selected without using any other additives, so as to ensure the high purity of the product.

[0005] The high-purity and high-sphericity iron powder of the present invention, wherein "high purity" means that the mass content is above 98%, preferably above 99%, and "high sphericity" means that the sphericity is above 98%, more preferably above 99%.

[0006] In order to achieve the above technical purpose, the present invention provides a method for producing high-purity and high-sphericity iron powder by hydrogen reduction-consolidation method, the method comprising the following steps:

[0007] 1) ultrafine grinding the iron oxide raw material to obtain a submicron ultrafine particle slurry, and the slurry is spray-dried to obtain spherical agglomerates;

[0008] 2) placing the spherical agglomerates in a reduction furnace for low-temperature hydrogen reduction at 300-475° C., and then placing them in a dynamic roasting furnace for high-temperature consolidation to obtain spherical iron powder agglomerates; during the high-temperature consolidation process, the rotation angular velocity of the dynamic roasting furnace is 0.3-1.5 r / min, and the temperature is slowly increased to 700-900° C. at a heating rate of no more than 30° C. / min for high-temperature consolidation, and then rapidly cooled to room temperature in an oxygen-free environment;

[0009] 3) The spherical iron powder agglomerates are broken up by ultrasound to obtain spherical iron powder with a purity of more than 98% and a sphericity of more than 98%.

[0010] In view of the technical defects of the prior art in which the spherical agglomerates of iron powder are directly subjected to hydrogen reduction and consolidation at a temperature of 750°C to 850°C, the key to the technical solution of the technical solution of the present invention is to adopt the method of low-temperature hydrogen reduction + dynamic high-temperature consolidation, which can effectively improve the surface morphology of spherical iron powder while achieving the reduction and consolidation of spherical agglomerates of iron powder, obtain spherical iron powder with high sphericity, high fluidity and smooth surface, and reduce the difficulty of dispersion of subsequent consolidated bodies. More specifically, the present invention first effectively avoids the growth of whiskers in the process of high-temperature reduction of iron powder by low-temperature reduction, achieves the improvement of the surface morphology of spherical iron powder spheres, is conducive to obtaining products with high sphericity, high fluidity and smooth surface, and adopts reasonable temperature rise and fall and dynamic process in the high-temperature consolidation process, which can effectively reduce abnormal agglomeration, breakage and pulverization during high-temperature treatment, and significantly improves the dispersion strength and yield rate required for the subsequent dispersion process.

[0011] As a preferred solution, the iron oxide raw material includes at least one of ultrapure iron concentrate and iron scale. The iron oxide raw material is mainly high-purity iron oxide concentrate, and the total mass content of impurities except oxygen does not exceed 1%. The iron oxide raw material is mainly ore raw materials or processed products of conventional metal smelting. In order to ensure the purity of iron powder, the mass content of impurities in the raw material is controlled to be less than 1% from the source. Of course, the higher the purity of the iron oxide raw material, the higher the purity of the prepared iron powder.

[0012] As a preferred solution, the ultrafine grinding adopts wet high-energy ball milling or wet nano sand milling. During the ultrafine grinding process, the particle size is controlled to meet the D50 particle size of submicron ultrafine particles between 100 and 500 nm, the particle size is normally concentrated, and the specific surface area is greater than 30 m 2 / g. The preparation process of spherical agglomerates mainly relies on the nucleation of fine particles during the spraying process, and also relies on the agglomeration of fine particles to consolidate, so the particle size requirement is relatively fine, and the smaller the original particle size, the better the sphericity and surface smoothness of the spherical agglomerates under the same conditions. In order to prepare higher performance spherical iron powder, the particle size of submicron ultrafine particles is controlled to be 100~500nm, and the further preferred particle size is controlled to be 100~200nm, and the corresponding specific surface area of ​​the particles is greater than 30m 2 / g, and the further preferred specific surface area range is 30~60 m 2 / g, and the parameters of ultrafine grinding also reflect the activity of submicron ultrafine particles in the reduction reaction and subsequent consolidation process. Only when the particle size meets the requirements can hydrogen reduction be effectively completed at low temperature. Wet high-energy ball milling or wet nano sand milling uses water or ethanol as the medium.

[0013] As a preferred solution, the spray drying adopts centrifugal spray drying, and the spray drying conditions are: the slurry solid content is 50-70% (solid content refers to the solid mass content), the slurry pumping rate is 30-100mL / min, the nozzle temperature is 200-300℃, and the sprayer speed is 15000-30000r / min. By adjusting the spray drying conditions, the diameter of the spherical agglomerates can be controlled to be 5-53µm, and the bulk density is not less than 1.4g / cm 3 . In order to improve the purity of spherical iron powder, no binder, plasticizer, dispersant, antioxidant coating agent or other additives are added to the slurry. Therefore, the slurry mainly improves the agglomeration ability of submicron ultrafine particles by controlling its solid content. The content of solvent in the slurry is related to the smooth operation of the subsequent spray drying process. The solid content needs to be controlled to 50~70% by rehydration or centrifugation, drying, sedimentation and other methods. No other reagents are added during the process, and the high purity characteristics of the product are guaranteed only by ensuring the agglomeration force of the submicron ultrafine particles themselves in the drying process. The spherical agglomerates formed by spray drying are aggregated by multiple submicron ultrafine particles. In spray drying, the dried groups are spherical due to the surface force. At present, the particle size of the dried powder of various spray dryers is basically below 100μm, and the fine powder limit is about 2 microns. However, the particle size of spherical agglomerates will directly affect the particle size of the final reduced iron powder product. The particle size is reduced during the reduction process, and the spherical iron powder with a particle size below 30μm has better application prospects and higher application value. Therefore, the preferred diameter of spherical agglomerates is determined to be 5~30µm. In order to produce spherical iron powder with higher density, high-density agglomerates need to be obtained in high-speed spray during the spray drying process. The corresponding particle size range should be 1.4~2.6g / cm 3 .

[0014] As a preferred solution, the reduction furnace is an electrically heated belt-type reaction furnace or a push-boat reaction furnace. The present invention has strict requirements on the reduction temperature, and it is recommended to use a steel belt-type or push-boat-type furnace with electric heating as the reduction reactor, which can make the spherical agglomerates heated evenly, and the reduction temperature difference does not exceed 1°C, and the reduction is more uniform.

[0015] As a preferred solution, the cloth thickness during the low-temperature hydrogen reduction process is 5 to 10 mm, and the hydrogen reduction time is 2 to 4 hours. Due to the low hydrogen reduction temperature, in order to ensure the thorough reduction of the iron powder, the material layer height should not be very high, and the height is preferably 5 to 10 mm. If the reduction temperature is too low during the low-temperature reduction process, it will lead to incomplete reduction, and if the reduction temperature is too high, whiskers are easily generated. However, the reduction temperature also controls the strength of the agglomerate, which has strict temperature requirements. If the reduction temperature is too low, it will also cause the strength of the spherical agglomerates to be difficult to meet the subsequent consolidation requirements. The reduction process is completely reduced by matching the reduction temperature with the time. The present invention controls the generation of iron whiskers as much as possible by controlling the reduction conditions, and realizes the transformation of iron oxides into iron phases in a stable and slow state, maintaining a smooth spherical surface after granulation, and at the same time making the iron powder particles after reduction have a certain strength to ensure stability during the subsequent rotary kiln roasting process.

[0016] As a preferred solution, the dynamic roasting furnace is a closed rotary kiln. Compared with the conventional high-temperature treatment on a steel belt machine, the high-temperature consolidation using a dynamic roasting furnace can complete the high-temperature consolidation between the particles inside the spherical agglomerates while maintaining the looseness between the spherical agglomerates, so that the material does not sinter or form hard lumps, the subsequent ultrasonic crushing is less difficult, the crushing process material yield is also higher, and the temperature tolerance of the furnace body such as a rotary kiln is often higher. When a dynamic rotary kiln is used for high-temperature treatment, it can also avoid the damage of the high temperature to the steel belt.

[0017] As a preferred solution, the high temperature consolidation is carried out in an inert or weakly reducing atmosphere, and the high temperature consolidation time is 30 to 90 minutes. The temperature of high temperature consolidation is further preferably 750 to 850°C. The high temperature solidified body is quickly cooled to room temperature in an oxygen-free environment, and the final oxygen content can be controlled to be no higher than 2000ppm. The iron powder has been initially formed after the reduction. If a rapid heating process is used, the expansion, breakage and even rupture of the sphere will be caused, affecting the powder yield and sphericity. After consolidation, the powder should be cooled rapidly without oxygen to reduce the risk of oxidation during the cooling process. The powder should be cooled in an inert atmosphere such as nitrogen / argon. When the material temperature is between 200 and 500°C, the cooling rate is maintained at more than 10°C / min, and the residual oxygen in the product after final cooling is no higher than 2000ppm.

[0018] As a preferred solution, at least one of water and alcohol is used as a medium during the ultrasonic beating process, the ultrasonic power is less than 1kW / L, and the time is less than 10min. Alcohols are low-carbon alcohols, such as ethanol. After the dynamic consolidation process, the bonding strength between the spherical iron powder particles is low, and the required ultrasonic dispersion difficulty is low, and dispersion can be achieved within a range of less than 1kW / L for 10min. Due to the low dispersion intensity, the destruction of the spherical particle structure by the strong dispersion process is also avoided. For the normal use of the equipment, intermittent ultrasound is often set, and the preferred implementation condition is to stop the ultrasound for 5s after 25s, and work in a cycle at this frequency.

[0019] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:

[0020] The present invention uses cheap iron oxide minerals as raw materials to prepare spherical iron powder by hydrogen reduction method. The process cost is much lower than that of atomization method or carbonyl method, and the whole process is green and pollution-free, and does not involve harsh reaction conditions such as high temperature and high pressure or toxic reagents.

[0021] The present invention prepares spherical agglomerates by spray drying, and the subsequent preparation process is divided into two steps for particle reduction and consolidation. Compared with the one-step reduction and consolidation method, the present invention solves key problems such as iron whisker growth in the one-step reduction method preparation process by optimizing and regulating the reduction-consolidation process parameters and coordinating the parameters. The prepared spherical iron powder has higher sphericity and fluidity, significantly improved surface smoothness, and better physical process performance.

[0022] The present invention controls the product particle size by regulating the slurry spraying and reduction-consolidation process. The particle size control is easier than that of the aerosol method or the carbonyl method. The particle size can be further optimized to below 10µm. The production cost of products of the same level is also much lower than that of the aerosol method and the carbonyl method.

[0023] The present invention adopts a dynamic high-temperature furnace body such as a rotary kiln to carry out the powder consolidation process, and adopts appropriate heating and cooling and consolidation process conditions to prevent the spherical powder from being damaged or seriously agglomerated. The subsequent ultrasonic dispersion process requires a short time and low power, which effectively reduces the probability of spherical powder breakage caused by high-intensity ultrasound. The high-temperature furnace body is used instead of equipment such as a belt furnace for high-temperature treatment, thereby avoiding the consumption of steel strips in a high-temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a morphology picture of the spherical iron powder prepared in Example 1.

[0025] Figure 2 This is the morphology of the spherical iron powder prepared in Example 2.

[0026] Figure 3 This is a morphology picture of the spherical iron powder prepared in Comparative Example 1.

[0027] Figure 4 This is a morphology picture of the spherical iron powder prepared in Comparative Example 2. DETAILED DESCRIPTION

[0028] In order to more clearly understand the present invention, specific embodiments are now used to more clearly explain and analyze the contents of the present invention. However, the claims of the present invention are not limited to the following example methods and conditions. Other examples obtained by relevant technical personnel in the field without creative work are all within the protection scope of the present invention.

[0029] Example 1

[0030] Ultrapure iron concentrate obtained by deep beneficiation was selected as raw material, with an iron grade of 72.1% and the total content of other impurities (acid insoluble matter) of only 0.3%. The material was finely ground in a nano sand mill, using a high-efficiency pin-type nano sand mill with a rotation speed of 2500r / min, 0.1mm zirconium oxide balls, ethanol as solvent, and a solid-liquid mass volume ratio of 1g:10mL. After 4 hours of grinding, an ultrafine particle slurry with a particle size of D50=100nm was obtained. The ethanol content of the slurry was adjusted to 50% by sedimentation and then entered the spray drying system. The slurry was dried in a centrifugal spray dryer to obtain a powder, wherein the slurry pumping rate was 100mL / min, the nozzle temperature was 270℃, and the sprayer speed was 27000r / min, and the diameter of the spherical agglomerates was about 30μm.

[0031] In the reduction stage of spherical agglomerates, the hydrogen reduction temperature was controlled at 300 °C, pure hydrogen was used as the reducing gas, and the spherical agglomerates were loosely distributed on the reduction steel belt with a spreading height of 5 mm and a reduction time of 4 h. After the reduction, the iron powder was only slightly agglomerated. After the steel belt was reduced, it entered the rotary kiln for reduction with an angular velocity of 0.3 r / min, the consolidation temperature was controlled at 700 °C, the heating rate was 10 °C / min, and the consolidation was performed for 90 min. After cooling, it was placed in the water phase and the material layer was dispersed by an ultrasonic cell disperser with a power set at 0.8 kW / L. The required dispersion time was about 5 min. The subsequent detection showed that the purity of the iron powder was 99.15%. The morphology image of the iron powder is shown in the figure. Figure 1 As shown; the figure shows that the spherical iron powder has good sphericity, smooth surface and dispersed particles, and has good overall performance.

[0032] Example 2

[0033] The raw material is steel scale produced in a certain place, with an iron grade of 72.4%. The main components are Fe2O3 and part of Fe. The characteristics are that the content of other impurities such as Al, Mn, Si is relatively high, and the total amount of impurity elements is 1%. The material is also finely ground in a nano sand mill. The model is a high-efficiency pin-type nano sand mill with a rotation speed of 2700r / min, the grinding beads are 0.3~0.4mm zirconium oxide balls, water is used as a solvent, and the solid-liquid mass volume ratio is 1g:3mL. After 2 hours of grinding, an ultrafine particle slurry with a particle size of D50=500nm is obtained. The ethanol content of the slurry is adjusted to 30% by sedimentation and then enters the spray drying system. The slurry is dried in a centrifugal spray dryer to obtain a powder, wherein the slurry pumping rate is 50mL / min, the nozzle temperature is 210℃, and the sprayer speed is 15000r / min, and the diameter of the spherical agglomerates is about 45μm.

[0034] In the reduction stage of spherical agglomerates, the hydrogen reduction temperature was controlled to be 475°C. The spherical agglomerates were loosely distributed on the reduction steel belt with a spreading height of 10 mm and a reduction time of 2 h. After the reduction, the iron powder was only slightly agglomerated. After the steel belt was reduced, it entered the rotary kiln for reduction with an angular velocity of 1.5 r / min. The consolidation temperature was controlled to be 900°C, the heating rate was 30°C / min, and the consolidation was performed for 30 min. The material layer was dispersed by an ultrasonic cell disperser in the water phase with the same power intensity of 0.8 kW / L. The required dispersion time was about 10 min. The subsequent detection showed that the purity of the iron powder was 98.8%. The morphology image of the iron powder is shown in FIG. Figure 2 As shown; the figure shows that the spherical iron powder maintains a high degree of sphericity and smoothness, and only a small amount of spherical iron powder has slight aggregation.

[0035] Comparative Example 1

[0036] The difference between this comparative example and Example 1 is that the reduction stage and the consolidation stage are different.

[0037] In the comparative example, the spherical agglomerates are subjected to a one-step high-temperature hydrogen reduction, and consolidation is simultaneously achieved during the reduction process. The hydrogen reduction temperature is controlled to be 700° C., and the time is 3 hours. Other conditions are consistent with those of Example 1. Spherical iron powder is obtained after the reduction is completed, and the iron powder is severely agglomerated after the reduction is completed.

[0038] The reduced product was placed in the water phase and dispersed into the material layer by an ultrasonic cell disperser. The power was the same as that in Example 1. The required dispersion time was about 10 min. The subsequent detection showed that the iron powder purity was 99.15%. The morphology of the spherical iron powder product was as follows: Figure 3 As shown in the figure, the surface iron whiskers of the spherical iron powder grow obviously, the sphericity decreases, and the performance is shown in Table 1 below.

[0039] Comparative Example 2

[0040] The difference between this comparative example and Example 2 is that static high-temperature consolidation is adopted.

[0041] The reduction temperature of the spherical agglomerates is controlled at 475℃ during the reduction stage. The agglomerates are loosely spread on the reduction steel belt with a spreading height of 10mm. The reduction is carried out for 2h. After the reduction, the iron powder is only slightly agglomerated. After the steel belt is reduced, it enters a static kiln with an angular velocity of 0r / min for total consolidation. The atmosphere is argon. The consolidation temperature is controlled at 900℃ for 30min. The material layer is dispersed by an ultrasonic cell disperser in the water phase. The crushing process is extremely difficult and requires 1.5kW / L ultrasonic power to break up. The required dispersion time is about 30min. The integrity of the spheres is also significantly affected during the crushing process, and about 7% of the mass ratio of broken fine powder will be produced. Its morphology is shown in the figure below. Figure 4 As shown in the figure, the spherical iron powder is seriously clumped and difficult to break up. During the forced breaking process, many spheres are broken, resulting in poor performance of the spherical iron powder product.

[0042] .

Claims

1. A method for producing high-purity and high-sphericity iron powder by hydrogen reduction-consolidation method, characterized in that: The following steps are involved: 1) ultrafine grinding the iron oxide raw material to obtain a submicron ultrafine particle slurry, and the slurry is spray-dried to obtain spherical agglomerates; 2) placing the spherical agglomerates in a reduction furnace for low-temperature hydrogen reduction at 300-475° C., and then placing them in a dynamic roasting furnace for high-temperature consolidation to obtain spherical iron powder agglomerates; during the high-temperature consolidation process, the rotation angular velocity of the dynamic roasting furnace is 0.3-1.5 r / min, and the temperature is slowly increased to 700-900° C. at a heating rate of no more than 30° C. / min for high-temperature consolidation, and then rapidly cooled to room temperature in an oxygen-free environment; 3) The spherical iron powder agglomerates are broken up by ultrasound to obtain spherical iron powder with a purity of more than 98% and a sphericity of more than 98%.

2. The method for producing high-purity and high-sphericity iron powder by hydrogen reduction-consolidation method according to claim 1, characterized in that: The iron oxide raw material includes at least one of ultrapure iron concentrate and iron scale.

3. The method for producing high-purity and high-sphericity iron powder by hydrogen reduction-consolidation method according to claim 1, characterized in that: The ultrafine grinding adopts wet high-energy ball milling or wet nano sand milling. During the ultrafine grinding process, the particle size is controlled to meet the D50 particle size of submicron ultrafine particles between 100 and 500 nm, the particle size is normally concentrated, and the specific surface area is greater than 30m 2 / g.

4. The method for producing high-purity and high-sphericity iron powder by hydrogen reduction-consolidation method according to claim 1 or 3, characterized in that: The spray drying adopts a centrifugal spray drying method, and the spray drying conditions are: the slurry solid content is 50-70%, the slurry pumping rate is 30-100 mL / min, the nozzle temperature is 200-300°C, and the sprayer speed is 15000-30000 r / min.

5. The method for producing high-purity and high-sphericity iron powder by hydrogen reduction-consolidation method according to claim 1, characterized in that: The reduction furnace is an electrically heated belt-type reaction furnace or a pusher-boat reaction furnace.

6. The method for producing high-purity and high-sphericity iron powder by hydrogen reduction-consolidation method according to claim 1 or 5, characterized in that: During the low-temperature hydrogen reduction process, the fabric thickness is 5-10 mm, and the hydrogen reduction time is 2-4 h.

7. The method for producing high-purity and high-sphericity iron powder by hydrogen reduction-solidification method according to claim 1, characterized in that: The dynamic roasting furnace is a closed rotary kiln.

8. The method for producing high-purity and high-sphericity iron powder by hydrogen reduction-consolidation method according to claim 1 or 7, characterized in that: The high temperature consolidation is carried out in an inert or weakly reducing atmosphere, and the high temperature consolidation time is 30 to 90 minutes.

9. The method for producing high-purity and high-sphericity iron powder by hydrogen reduction-consolidation method according to claim 1, 2, 3, 5 or 7, characterized in that: During the ultrasonic dispersion, at least one of water and alcohol is used as a medium, the ultrasonic power is less than 1 kW / L, and the time is less than 10 minutes.